2014
DOI: 10.1071/en13221
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic toxicity of manufactured nanomaterials: challenges and recommendations for future toxicity testing

Abstract: Environmental context. The increased use of nanomaterials in industrial and consumer products requires robust strategies to identify risks when they are released into the environment. Aquatic toxicologists are beginning to possess a clearer understanding of the chemical and physical properties of nanomaterials in solution, and which of the properties potentially affect the health of aquatic organisms. This review highlights the main challenges encountered in aquatic nanotoxicity testing, provides recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 200 publications
(331 reference statements)
0
39
0
2
Order By: Relevance
“…A growing number of studies suggest that organic (e.g., proteins, metabolites, lipids, DNA, and other natural substances) and/or inorganic (e.g., artificial waters, electrolytes, buffers) components in the exposure media can disturb the dissolution of NMs [49]. It is no longer acceptable to measure dissolution of NMs solely in media or solutions other than those being used in the exposure test [10]. Still, the complexity of the nano-bio interactions will create difficulties in the assessment of NMs dissolution in exposure media, especially in the presence of test organisms.…”
Section: Factors That Affect the Assessment Of Nms Dissolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…A growing number of studies suggest that organic (e.g., proteins, metabolites, lipids, DNA, and other natural substances) and/or inorganic (e.g., artificial waters, electrolytes, buffers) components in the exposure media can disturb the dissolution of NMs [49]. It is no longer acceptable to measure dissolution of NMs solely in media or solutions other than those being used in the exposure test [10]. Still, the complexity of the nano-bio interactions will create difficulties in the assessment of NMs dissolution in exposure media, especially in the presence of test organisms.…”
Section: Factors That Affect the Assessment Of Nms Dissolutionmentioning
confidence: 97%
“…), and so on [9]. Meanwhile, the kinetics of dissolution and the saturation concentration are affected by conditions of the surrounding media (e.g., pH, ionic strength, water hardness) and the presence of bio-components (e.g., natural organic matter, polysaccharides, proteins, and the test organism) [9,10].…”
Section: Nms Dissolution At the Nano-bio Interfacementioning
confidence: 99%
“…It is necessary to strengthen the research on the physicochemical transformation of NPs in a real water environment for the scientific assessment of environmental behaviors and biological effects of the NPs. An increasing number of studies have reported the toxicity of NPs to aquatic organisms with a focus on the effect of water chemistry (Schultz et al, 2014). The higher toxicity of Ag NPs to algal cells was observed in acidic media (Oukarroum et al, 2014) and media with high ionic strength (Chambers et al, 2014), owing to the increased release of silver ions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, environmental concentrations of some NPs in their application or deposition area could be extremely high, e.g., 0.75e50 g/L zero valent iron NPs were used in in situ field scale remediation of contaminated soil and groundwater (Grieger et al, 2010). More and more case studies indicated that the discharged NPs could pose serious risks to aquatic organisms (Ma et al, 2013;Schultz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Schultz et al [4] outline some of the challenges presented by transformations of MNMs and make recommendations for future toxicity testing. They review the toxicity data for the three most commonly studied metal-based MNMs (TiO 2 , Ag and ZnO) and highlight the emerging themes in the aquatic toxicology of these materials.…”
mentioning
confidence: 99%